Climate change, drought and rural communities: Understanding people's perceptions and adaptations in rural eastern India. (April 2020) - Sam, Anu Susan; Padmaja, Subash Surendran; Kächele, Harald; Kumar, Ranjit; Müller, Klaus
Abstract: Household's adaptation to drought risk consists of two steps. First step is acquiring knowledge on drought from previous drought experiences. Second step is formulation of local adaptation measures that can reduce drought risk. Lack of knowledge regarding households' perception about droughts and local adaptation measures are identified as barriers in formulating effective adaptation strategies and polices. Therefore, this paper aims to gather information on households' perceptions about drought impacts and local adaption and coping measures. We also analysed the potential determinants that affect the household's preferences for future adaptation and coping strategies. Data for the study was collected from 157 drought prone rural households of Odisha state in India. We employed both qualitative and quantitative methods to analyze the data. The major impacts of drought reported by rural people were the yield reduction/loss and issues of various diseases during drought. Although more than half of rural households reported adverse effects of drought, it was not their predominate concern. The most common coping measure adopted by the rural people during drought was reduction in the consumption of rice/cereals. The results indicate that rural people prefer to follow reduction in the food consumption strategy in future also. Family size, gender and education of household head and distance to nearby town influenced the preference of adaptation and coping strategies. This research can stand as one mainstay in providing insights to researches and policy makers in formulating strategies and policies for vulnerability reduction in rural India. Highlights: Adaption is the ability to deal with the projected impacts of climate change and natural hazards. Rural people have experienced significant changes in temperature and rainfall. Most people/farmers perceived drought would lead to yield reduction and disease infestation. Rice and cereals consumption reduction was the most frequently adopted coping measure during drought period. Gender and education of household head are correlated with the decision to adopt particular adaptation strategy.